solving an equation using order of operations

Jun 2016
4
0
california
[FONT=&quot](2+1)[/FONT][FONT=&quot]{[(4+4)2+3](1)7}[/FONT]
 

Debsta

MHF Helper
Oct 2009
1,343
620
Brisbane
What do you get? Show us your steps and, if necessary, we'll show you where you are going wrong.
 
Jun 2016
4
0
california
(2+1){[(0)+3](−1)−7}
(2+1){[3](−1)−7}
(3){[3](−1)−7}
9*7
the 2 +3 the 2 is an exponent by the way
 

Debsta

MHF Helper
Oct 2009
1,343
620
Brisbane
(2+1){[(0)+3](−1)−7}
(2+1){[3](−1)−7}
(3){[3](−1)−7}
9*7
the 2 +3 the 2 is an exponent by the way
There is an understood multiplication sign between 3 and -1
 
Jun 2016
21
4
india
(2+1){[(-4+4)2+3](-1)-7}
Apply PEMDAS rule to follow the order of operations
P=parantheses, E=exponents, M=multiplication, D=division, A=addition , and then S= subtraction.
So, we solve parentheses first
= 3{[(0)2+3](-1)-7}
= 3{[3](-1)-7}
= 3{-3-7}
= 3{-10}
= -30
It is the solution of this expression.
 

HallsofIvy

MHF Helper
Apr 2005
20,249
7,909
That's an arithmetic problem. There is no "equation" to solve.
 
Sep 2016
84
19
India
[FONT="][FONT=MJXc-TeX-main-R]([/FONT][FONT=MJXc-TeX-main-R]2[/FONT][FONT=MJXc-TeX-main-R]+[/FONT][FONT=MJXc-TeX-main-R]1[/FONT][FONT=MJXc-TeX-main-R])[/FONT][/FONT][/COLOR][COLOR=#000000][FONT="]{[(4+4)2+3](1)7}[/FONT]
First of all it's an expression because there is no equal sign.
Now, solve it using order of operation, i.e., PEMDAS(Parenthesis, Exponent, Multiplication, Division, Addition, Subtraction)
$(2+1)\{[(-4+4)^{2+3}](-1)-7\}$

Solve the parenthesis first,
$3\{[(0)^5](-1)-7\}$

Now exponent
$3\{[0](-1)-7\}$

similarly follow the rule(PEMDAS)

$3\{0-7\}$

$3\{-7\}$

$=-21$
 
Last edited: